PEMANFAATAN LIMBAH Sargassum polycystum DARI INDUSTRI FARMASI SEBAGAI PUPUK CAIR SERTA PENGARUHNYA TERHADAP SIFAT KIMIA TANAH ULTISOL DAN PERTUMBUHAN TANAMAN SAWI - Hafsah Winda Nst1 Hafsah Winda Nst1 Hafsah Winda Nst1; Alida Lubis; Supriadi Supriadi (Universitas Sumatera Utara, 2013)
The aim of this research to know the effect of seaweed liquid fertilizer (Sargassum polycystum) made ​​from waste materials on the growth and production of mustard (Brassica juncea L.) on ultisol. This research was held in gauze house, Chemistry/Soil Fertility Laboratory and Research Laboratory, Agricultural Faculty, University of North Sumatra, Medan in June-September 2012. The sample of soil to used is ultisol. The research used a Completely Randomized Design (CRD) Non Factorial with nine treatments and three replications that are twenty-seven experimental units. Treatment consists of P0 (Control), Pa2 (EM-4 20 cc with liquid seaweed fertilizer every 2 days), Pa3 (EM-4 20 cc with liquid seaweed fertilizer every 3 days), Pa4 (EM-4 20 cc with liquid seaweed fertilizer every 4 days), Pa5 (EM-4 20 cc with liquid seaweed fertilizer every 5 days), Pb2 (EM-4 40 cc with liquid seaweed fertilizer every 2 days), Pb3 (EM-4 40 cc with liquid seaweed fertilizer every 3 days), Pb4 (EM-4 40 cc with liquid seaweed fertilizer every 4 days), Pb5 (EM-4 40 cc with liquid seaweed fertilizer every 5 days). The result of experiments showed that seaweed liquid fertilizer different is not real to pH of soil, C-organic of soil, N soil, K-exchange, C/N of soil. But, real different to the P-available of soil, fresh weight of plants, fresh weight of root, dry weight of plant and dry weight of root. Keywords: Polycystum sargassum, Seaweed fertilizer, Mustard (Brassica juncea L).